Massive cutaneous complications due to snakebite: A case report and literature review - Sadeghi, Mahdieh; Barazandeh, Maryam; Zakariaei, Zakaria; Davoodi, Lotfollah; Tabaripour, Rabeeh; Fakhar, Mahdi; Zakariaei, Ashkan (Clinical case reports, 2021)
Wound infections due to snake bites such as cellulitis and necrotizing fasciitis, although not common, are seen in snake bites and if left untreated can cause serious complications. Wound infections due to snake bites such as cellulitis and necrotizing fasciitis, although not common, are seen in snake bites and if left untreated can cause serious complications.